2017
DOI: 10.3892/or.2017.5958
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-mediated human aryl hydrocarbon receptor mRNA translation by an internal ribosomal entry site-dependent mechanism

Abstract: The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor that is best known in mediating the toxicities of dioxins and dioxin-like compounds. AHR is activated by a variety of endogenous ligands and participating in tumor development. Thus, it will provide a new approach for cancer prevention and treatment to study the translation mechanism of AHR in tumor cells. In this study, we show that the 5'-untranslated region (UTR) of AHR mRNA contains an internal ribosome entry site (IRES). After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Our data demonstrate that riluzole can display synergistic anti-GBM effects with mTOR inhibitors (see Figure 5C) and recent data have demonstrated that riluzole synergizes with the chemotherapeutic paclitaxel in triple-negative breast cancers [53]. It is well known that chemotherapeutically induced cellular stress can activate IRES-mediated protein synthesis of various transcripts, including the aryl hydrocarbon receptor, ATF2, ribosome binding protein 1, c-myc and β-catenin [54][55][56][57][58]. While c-myc IRES-dependent translation is mediated via hnRNP A1, it is tempting to speculate that these other IRES containing mRNAs may also be regulated via hnRNP A1 activity and that these compounds may be utilized to identify other transcripts subject to hnRNP A1-mediated IRES regulation.…”
Section: Discussionsupporting
confidence: 74%
“…Our data demonstrate that riluzole can display synergistic anti-GBM effects with mTOR inhibitors (see Figure 5C) and recent data have demonstrated that riluzole synergizes with the chemotherapeutic paclitaxel in triple-negative breast cancers [53]. It is well known that chemotherapeutically induced cellular stress can activate IRES-mediated protein synthesis of various transcripts, including the aryl hydrocarbon receptor, ATF2, ribosome binding protein 1, c-myc and β-catenin [54][55][56][57][58]. While c-myc IRES-dependent translation is mediated via hnRNP A1, it is tempting to speculate that these other IRES containing mRNAs may also be regulated via hnRNP A1 activity and that these compounds may be utilized to identify other transcripts subject to hnRNP A1-mediated IRES regulation.…”
Section: Discussionsupporting
confidence: 74%
“…AHR activation mediated by the endogenous ligand FICZ induces the expression of genes associated with migration, invasion, and stemness in triple-negative BC cells [ 42 ]. Furthermore, functional studies of AHR in CSCs have shown that it contributes to the chemoresistance of CSCs [ 43 , 44 , 45 ]. The expression of chemotherapy resistance-related transporter (such as ABCG2)- and enzyme (such as aldo-keto reductase 1C3 and ALDH1A1)-encoding genes, which are AHR-target genes, is increased in AHR-overexpressing CSCs [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, functional studies of AHR in CSCs have shown that it contributes to the chemoresistance of CSCs [ 43 , 44 , 45 ]. The expression of chemotherapy resistance-related transporter (such as ABCG2)- and enzyme (such as aldo-keto reductase 1C3 and ALDH1A1)-encoding genes, which are AHR-target genes, is increased in AHR-overexpressing CSCs [ 43 , 44 , 45 ]. Previous reports, including our studies, have established the anti-tumorigenic ability of agonist-activated AHR [ 46 ].…”
Section: Discussionmentioning
confidence: 99%